RETRACTED: ANALISIS POTENSI PENGHEMATAN AIR PDAM DENGAN SISTEM PEMANENAN AIR HUJAN DI RUSUNAWA MUARA BARU - Michael Randy Raharja; Arianti Sutandi; Vittorio Kurniawan (JMTS: Jurnal Mitra Teknik Sipil, 2021)
Rainwater is so abundant, more wasted than used. This writing aims to determine the volume of water that can be accommodated in the roof area of the rain catchment by calculating the area of the roof and daily rainfall, then calculating the optimal size of the reservoir according to the manufacturing costs using the payback period method and to find out the large percentage of potential water and cost savings. Water-saving. From the calculation, the largest amount of water that can be accommodated in 2019 is in January of 422.36 m3 and 2020 in February of 1152.81 m3. By calculating the payback period, the optimal size of the reservoir is 75 m3. Based on the results of the analysis of cost savings from the amount of water collected, with a tank size of 330 m3, it was found that the savings that occurred in 2019 amounted to IDR 12,843,152.60. The savings that occur from 2020 to August are IDR 19,127,241.30. Based on the calculation of the percentage of efficiency according to data on water use, the average efficiency in 2019 is 4%, and in 2020 it is 7.7%.  Air hujan yang begitu berlimpah, lebih banyak terbuang percuma dibanding untuk dimanfaatkan. Penulisan ini bertujuan untuk mengetahui volume air yang dapat ditampung di area atap tangkapan hujan dengan menghitung luasan atap dan curah hujan harian, lalu menghitung besar bak penampung yang optimal sesuai dengan biaya pembuatan dengan menggunakan metode payback period dan untuk mengetahui persentase besar potensi penghematan air dan biaya penghematan air. Dari perhitungan, jumlah air yang mampu ditampung terbesar tahun 2019 pada bulan Januari sebesar 422,36 m3 dan tahun 2020 pada bulan Februari sebesar 1152,81 m3. Dengan perhitungan payback period, didapat ukuran bak penampungan optimal adalah sebesar 75 m3. Berdasarkan hasil analisis penghematan biaya dari jumlah air yang ditampung, dengan ukuran bak 330 m3 didapat bahwa penghematan yang terjadi pada tahun 2019 adalah sebesar Rp12.843.152,60. Untuk penghematan yang terjadi pada tahun 2020 sampai bulan Agustus adalah sebesar Rp19.127.241,30. Berdasarkan hasil perhitungan persentase efisiensi menurut data pemakaian air efisiensi rata-rata tahun 2019 adalah sebesar 4% dan tahun 2020 sebesar 7,7%.